Quality Of Lighting In Regular And Fullday Class Tsanawiyah Miftahul Huda Tayu Pati - Solichah, Solichah; Yulianti, Ian (Physics Communication, 2022)
An analysis of the quality of the lighting level in the classroom needs to be carried out to determine the existing lighting level. If the level of lighting is below the specified standard, it can cause eye damage.  Meanwhile, if the level of lighting is above the standard, the classroom will be too bright. The purpose of this study was to determine the level of lighting in the Regular and Full Day classroom of  MTs. Miftahul Huda Tayu. The tools and materials used in this experiment are lux meter, roller meter and thermohygro. The experiment was carried out in the Regular class school building and the Full Day classroom building with a sample of three rooms per building with each room representing each floor. The experiment was carried out during the day for three consecutive days. There are two types of the intensity measured in this experiment, namely natural intensity (lights off) and natural artificial intensity (lights on). In each room, 9 points were taken. The floor area and window area were measured using a roller meter. From the experiments that have been carried out, it can be concluded that the lighting in the Regular class (17-73 lux) and Full Day class (97-181 lux) buildings do not meet Indonesian National standards (Standar Nasional Indonesia, SNI).